THE IMPACT OF EFFECTIVE TIME USE ON THE PSYCHOLOGICAL ADAPTATION AND RESILIENCE OF INTERNALLY DISPLACED PERSONS (Psychology Travelogs, 2025)
The article presents the results of a theoretical and empirical study aimed at assessing the effectiveness of a preventive and corrective program for emotional burnout among psychologist-trainers under wartime conditions in Ukraine. The research involved 36 participants and applied the Maslach Burnout Inventory (MBI), the Professional Identity Diagnostic Method (A. Kulagina adaptation), and the Perceived Stress Scale (PSS-10). The analysis revealed statistically significant positive changes across all measured dimensions: emotional exhaustion decreased by an average of 6.7 points, depersonalization by 3.8 points, and the sense of personal accomplishment increased by 4.5 points. The implementation of the program contributed to reduced stress perception, enhanced confidence in professional roles, and strengthened internal coping mechanisms. Correlation analysis confirmed inverse relationships between emotional exhaustion and professional identity (r = –0.62; p < 0.01), demonstrating that self-awareness and value coherence act as protective resources against burnout. The findings highlight that structured preventive interventions, including relaxation, visualization, and self-reflection exercises, effectively restore emotional balance and resilience among helping professionals. The developed model has proven efficient not only for psychologists but can also be adapted for educators, social workers, and healthcare providers exposed to chronic stress. The program was implemented in a hybrid format combining group training sessions and individual reflection tasks, which ensured accessibility for specialists displaced by the war. Its results emphasize the pedagogical and social value of developing systematic psychological support frameworks within professional education to enhance resilience and long-term well-being in crisis contexts.
Keywords: emotional burnout; professional identity; psychological resilience; perceived stress; prevention; psychologist-trainers; mental well-being